Attention Deficit-Hyperactivity Disorder Symptoms and Daytime Voiding Symptoms in Children with Primary Enuresis: An Observational Study to Evaluate the Effectiveness of Desmopressin Treatment - Teng-Kai Yang; Ya-Jun Guo; Hong-Chiang Chang; Hung-Ju Yang; Kuo-How Huang (The Scientific World Journal)
Purpose. To evaluate the effectiveness of presence of desmopressin in treating primary enuresis (PE) for children with attention deficit-hyperactivity disorder (ADHD) symptoms. Materials and Methods. Children aged from 5 to 12 years with the chief complaint of PE treated with desmopressin were enrolled in pediatric urology clinics. The parent-reported SNAP-IV questionnaire was used to evaluate ADHD symptoms (cut-off value: 90th percentile). Voiding symptoms were assessed by the Dysfunctional Voiding Scoring System (DVSS) questionnaire. The responses to desmopressin were analyzed in children with and without ADHD symptoms. Results. The study sample comprised 68 children; 27 (39.7%) presented with ADHD symptoms and 41 (60.3%) with non-ADHD symptoms. The children collected from a tertiary referral center may explain the high prevalence of ADHD symptoms in the present study. The total DVSS score in the ADHD symptoms group was significantly higher than in the non-ADHD symptoms group (7.72 versus 5.65, P=0.05). In the ADHD symptoms group, there were significantly higher score in the “pee 1-2 times/day” and “can’t wait” subscales of DVSS and lower sleep quality based on the Pediatric Sleep Quality questionnaire, as well as significantly lower peak flow rate and voided volume. The responses to desmopressin for enuresis were comparable between children with ADHD and non-ADHD symptoms. Conclusions. Approximately 39.7% of PE children presented with ADHD symptoms at urologic clinics. PE children with ADHD symptoms had higher risk of daytime LUTS and comparable response to desmopressin treatment for PE. To evaluate ADHD symptoms and daytime voiding symptoms is important in children with PE.